Short‐Term Forecasts of French GDP: A Dynamic Factor Model with Targeted Predictors. (25th June 2013) - Bessec, Marie
ABSTRACT: In recent years, factor models have received increasing attention from both econometricians and practitioners in the forecasting of macroeconomic variables. In this context, Bai and Ng ( Journal of Econometrics 2008;146 : 304–317) find an improvement in selecting indicators according to the forecast variable prior to factor estimation ( targeted predictors ). In particular, they propose using the LARS‐EN algorithm to remove irrelevant predictors. In this paper, we adapt the Bai and Ng procedure to a setup in which data releases are delayed and staggered. In the pre‐selection step, we replace actual data with estimates obtained on the basis of past information, where the structure of the available information replicates the one a forecaster would face in real time. We estimate on the reduced dataset the dynamic factor model of Giannone et al. ( Journal of Monetary Economics 2008;55 : 665–676) and Doz et al. ( Journal of Econometrics 2011;164 : 188–205), which is particularly suitable for the very short‐term forecast of GDP. A pseudo real‐time evaluation on French data shows the potential of our approach. Copyright © 2013 John Wiley & Sons, Ltd.